Alcoholic hepatitis: Translational approaches to develop targeted therapies. Issue 4 (15th April 2016) - Mandrekar, Pranoti; Bataller, Ramon; Tsukamoto, Hidekazu; Gao, Bin
Abstract : Alcoholic liver disease is a leading cause of liver‐related mortality worldwide. In contrast to recent advances in therapeutic strategies for patients with viral hepatitis, there is a significant lack of novel therapeutic options for patients with alcoholic liver disease. In particular, there is an urgent need to focus our efforts on effective therapeutic interventions for alcoholic hepatitis (AH), the most severe form of alcoholic liver disease. AH is characterized by an abrupt development of jaundice and complications related to liver insufficiency and portal hypertension in patients with heavy alcohol intake. The mortality of patients with AH is very high (20%‐50% at 3 months). Available therapies are not effective in many patients, and targeted approaches are imminently needed. The development of such therapies requires translational studies in human samples and suitable animal models that reproduce the clinical and histological features of AH. In recent years, new animal models that simulate some of the features of human AH have been developed, and translational studies using human samples have identified potential pathogenic factors and histological parameters that predict survival. Conclusion : This review summarizes the unmet needs for translational studies on the pathogenesis of AH, preclinical translational tools, and emerging drug targets to benefit the AH patient. (Hepatology 2016;64:1343‐1355)